Republic of Uzbekistan : Technical Assistance Report-Fiscal Transparency Evaluation Update. (IMF Staff Country Reports; Country Report ;, 2019)
This Fiscal Transparency Evaluation report on the Republic of Uzbekistan provides a summary of progress made since that evaluation was conducted and is based on practices in place at the time of a Fiscal Affairs Department visit. Uzbekistan has improved its fiscal transparency practices against eight of the Code's standards since the June evaluation. Most improvements have been accomplished in the areas of fiscal forecasts and budgeting, and fiscal risk disclosure. A road map has also been developed to expand the coverage and quality of fiscal reports and better align these with international standards, further enhance fiscal risk disclosure, and ensure greater parliamentary scrutiny of the budget. Work has also commenced to identify all off-budget fiscal activities, and, the government has committed to including these in future budget and government finance statistics (GFS) reports. Efforts are also underway to expand the coverage of GFS reports, so that they reflect all general government fiscal transactions, including those of nonmarket state-owned enterprises.